Economic and environmental design optimisation of reinforced concrete frame buildings: A comparative study. (April 2022) - Negrin, Iván A.; Chagoyén, Ernesto L.
Abstract: This paper presents the economic and environmental design optimisation of three-dimensional reinforced concrete frame buildings using Biogeography-Based Optimisation, a relatively new methodology that is well suited to allow for discrete optimisation problems. In addition to monetary cost, embodied energy (EE) and CO2 emissions were used as objectives. The results showed that the literature on related studies is very extensive, with many different case studies and objectives under analysis, making it very difficult to unify criteria and to obtain specific design recommendations. However, it is clear that these three objectives are not contradictory, i.e., optimisation using each of them as an objective leads to good results as measured by the others. These results depend mainly on the cost ratio R between steel and concrete. We were able to identify some recommendations based mainly on the variations of R.